Revisiting the Prohibition of Khamr and Maysir in the Qur’an: An Examination of Surah Al-Mā’idah [5]: 90-91 - Rustriningsih; Fejrian Yazdajird Iwanebel (IAIN Madura, 2024)
This article delves into the unequivocal prohibition of drunkenness and gambling in Islam, as elucidated in the Qur’an Surah al-Mā’idah [5]: 90-91. While the Quranic prohibition clearly labels certain actions as ‘rijs’ (abominable acts) and associates them with the deeds of the devil, contemporary scholars often prioritize historical and juridical analyses over examining the relevance of these verses in the present day. Thus, this article endeavors to enhance interpretation by situating the text within both its historical context and contemporary circumstances. By employing the ma‘nā-cum-maghzā approach, which equally considers the verse’s historical background and the contemporary reader’s context, the article posits that the prohibition on khamr (intoxicants) and all forms of gambling transcends mere restriction to constitute a ‘binding prohibition.’ This assertion is substantiated by the identification of inherent implications significantly correlated with these proscribed acts, encompassing the promotion of temporal respect, avoidance of diverse adverse impacts on health, economy, social relations, and religious facets, as well as a deterrent against arrogance and mutual reproach.